Quantum mechanics solver how to apply quantum theory to modern physics - Basdevant Jean-Louis; Dalibard Jean (Berlin Springer-Verlag, 2006)
This book uniquely illustrates the application of quantum mechanical concepts to various fields of modern physics. It aims at encouraging the reader to apply quantum mechanics to research problems in fields such as molecular physics, condensed matter phy
Keywords: Quantum theory>Problems, exercises>